Air Pollution and Respiratory Health in Benghazi, Libya: A Cross-Sectional Study of Environmental and Public Health Perspectives on Cement Factory Emissions - Omar, Emad (Sharwes Scientific Journal, 2025)
Industrial air pollution, particularly from cement manufacturing, continues to raise critical public health concerns in Libya’s urban centres. This study examined the perspectives of healthcare, environmental, and regulatory professionals in Benghazi regarding the respiratory health implications of emissions produced by the local cement factory. The investigation focused on expert assessments of pollutant exposure, levels of public awareness, and the perceived adequacy of regulatory enforcement. A cross-sectional survey was conducted between March and May 2025 using a structured and validated online questionnaire. The instrument comprised four sections: demographic characteristics (6 items), perceived respiratory health impact (8 items), public awareness and communication (10 items), and regulatory monitoring and enforcement (10 items). A total of 600 participants were purposively selected from three stakeholder groups: healthcare providers, environmental experts, and regulatory personnel, with 200 individuals from each group. Data were analysed using SPSS Version 27, incorporating descriptive statistics and Pearson’s correlation tests. Ethical approval was granted by the Benghazi Cement Factory’s Administrative Board. Most respondents (74.2%) agreed that factory emissions are linked to increased respiratory conditions in nearby communities. Furthermore, 65.1% cited inadequate environmental communication as a key barrier to improving public awareness, while 78.7% expressed low confidence in regulatory performance. Correlation analysis revealed a moderate positive association between perceived emissions exposure and respiratory health concerns (r = 0.219, p = 0.007), with weaker but significant relationships observed for public awareness (r = 0.183, p = 0.021) and enforcement mechanisms (r = 0.197, p = 0.014). These findings highlight health risks and communication and regulatory deficiencies needing targeted policy attention.